Objektni pristop k prenovitvi poslovanja - Črv, Milan (Uporabna informatika (Ljubljana), 2000)
The aim of the paper is to introduce an object-oriented method called Object-Oriented Approach to Business Transformation. The proposed approach represents a general framework for implementation of transformation process and recommends the use of several generally known and verified techniques. Theprocess cycle has four main phases. The first phase involves the preparation of the environment. The second phase includes analysis of the existing process and development of a model of the new process and its information system. In the third phase, the existing organizational structure is revised. The last phase deals with the implementation of the new process.
Keywords: informatika; pilotni model; poslovni sistemi; reorganizacija